FEASIBILITY STUDY PERKEMBANGAN NFT (NON FUNGIBLE TOKEN) SEBAGAI SALAH SATU INSTRUMEN INVESTASI DI BIDANG TEKNOLOGI - Dewa Gede Ari Setyawan; Anak Agung Elik Astari; Ni Luh Indiani (Nusantara Hasana Journal, 2022)
The development of digital-based technology in the millennium era has implications for the development of various forms of digital-based investment and digital-based investment instruments. This study aims to determine the feasibility of developing NFT (Non-Fungible Token) as an investment instrument in the technology sector. With the development of NFT (Non Fungible Token) as an investment instrument in the technology sector, it is able to support people's financial problems during the Covid-19 pandemic. NFT (Non Fungible Token) is an investment instrument in the form of crypto assets that are in demand by the millennial generation because it requires minimal capital and large profits. This study uses qualitative data analysis techniques, data obtained through literature studies, interviews, and documentation conducted with investment actors who use NFT (Non-Fungible Token) as an investment instrument. The feasibility analysis uses financial aspects, and non-financial aspects, namely marketing aspects, legal aspects and economic aspects. The results of this study indicate that the development of NFT (Non-Fungible Token) as an investment instrument in the technology sector is feasible to be developed based on a review of aspects of feasibility analysis.